2019
DOI: 10.1080/15427528.2019.1606129
|View full text |Cite
|
Sign up to set email alerts
|

Yield determination of maize hybrids under limited irrigation

Abstract: Hybrid adoption, irrigation, and planting density are important factors for maize (Zea mays L.) production in semiarid regions. For this study, a 2-yr field experiment was conducted in the Texas High Plains to investigate maize yield determination, seasonal evapotranspiration (ETc), and water-use efficiency (WUE) under limited irrigation. Two hybrids (N74R, a conventional hybrid, and N75H, a drought-tolerant (DT) hybrid) were planted at three water regimes (I 100 , I 75 , and I 50 , referring to 100%, 75%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In this 3-yr study, we were not able to detect significant differences in grain or biomass yield among the three maize hybrids. Other field studies in the THP (Mounce et al, 2016;Zhao et al, 2019) observed similar yield responses but for differing hybrid comparisons. In contrast, Hao, Xue, Marek, Jessup, Hou, et al (2015) concluded that significant yield benefits could be obtained with a drought-tolerant P1151 compared with conventional hybrid (33D49) under water-limited conditions.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In this 3-yr study, we were not able to detect significant differences in grain or biomass yield among the three maize hybrids. Other field studies in the THP (Mounce et al, 2016;Zhao et al, 2019) observed similar yield responses but for differing hybrid comparisons. In contrast, Hao, Xue, Marek, Jessup, Hou, et al (2015) concluded that significant yield benefits could be obtained with a drought-tolerant P1151 compared with conventional hybrid (33D49) under water-limited conditions.…”
Section: Discussionmentioning
confidence: 60%
“…In this 3‐yr study, we were not able to detect significant differences in grain or biomass yield among the three maize hybrids. Other field studies in the THP (Mounce et al., 2016; Zhao et al., 2019) observed similar yield responses but for differing hybrid comparisons. In contrast, Hao, Xue, Marek, Jessup, Hou, et al.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Comparisons of drought with nondrought-tolerant hybrids have sometimes shown no differences in water use and grain yields (Nielsen & Schneekloth, 2018). Other researchers have observed some differences in crop water use patterns (Hao, Xue, Marek, Jessup, Becker, et al, 2015;Mounce et al, 2016;Zhao et al, 2018) but typically with no yield advantages under water deficit (Mounce et al, 2016;Zhao et al, 2018;Zhao et al, 2019). In these irrigated field studies, crop water stress was achieved during the growing season by imposing a targeted stress level at particular crop development stages or by adjusting irrigation levels based on a constant crop evapotranspiration (ET a ) as a fraction of fully irrigated crop ET (ET m ).…”
Section: Core Ideasmentioning
confidence: 99%